Association of R279Q and C1562T polymorphisms of matrix metalloproteinase 9 gene and increased risk for myocardial infarction in patients with premature coronary artery disease - Sheikhvatan, Mehrdad (J Clin Lab Anal, 2017)
BACKGROUND: A number of matrix metalloproteinase (MMP) gene polymorphisms has been identified which may be probably related to premature myocardial infarction (MI). OBJECTIVE: We assessed the relationship between the two polymorphisms of the MMP9 gene including R279Q and C1562T and occurrence of premature MI. METHODS: The study has two phases including a case‐control study as the first phase and cohort study as the second phase. Initially, 1000 patients with premature coronary artery disease were classified into MI and non‐MI groups. Genotyping of the polymorphism was conducted by PCRRFLP and high‐resolution melting techniques. Given the two conditions of patients residing in Tehran and faced with their first episode of MI, 640 of 1000 study samples previously followed up with a median follow‐up time of 45.74 months were assessed in a retrospective cohort phase regarding long‐term major adverse cardiac events (MACE). RESULTS: The prevalence of wild, heterozygous, and mutant genotypes of R279Q polymorphism in MI group was 14.5%, 57.3%, and 28.2% and in non‐MI group was 36.9%, 38.4%, and 24.7%, respectively, with a considerable difference (P<.001). There was a significant difference in the prevalence of wild, heterozygous, and mutant genotypes of C1562T polymorphisms in MI group (12.4%, 41.2%, and 46.4%, respectively) and in non‐MI group (46.8%, 38.6%, and 14.7%, respectively; P<.001). No difference was found in total MACE‐free survival rate between genotypes of R279Q and C1562T polymorphisms. CONCLUSION: C1562T and R279Q polymorphisms are associated with the susceptibility to premature MI, but cannot predict long‐term cardiac events in these patients.